Clinical characteristics of polycystic ovary syndrome in Indian women - Sunita J Ramanand; Balasaheb B Ghongane; Jaiprakash B Ramanand; Milind H Patwardhan; Ravi R Ghanghas; Suyog S Jain (Indian Journal of Endocrinology and Metabolism, 2013)
Background: Polycystic ovary syndrome (PCOS) is common diagnosis in women presenting with infertility. All the dimensions of PCOS have not been completely explored. Many studies have tried to characterize the exact presentation of the disease. In this study we studied clinical features of PCOS in Indian women to characterize different phenotypes of this syndrome. Prevalence of acanthosis nigricans (AN) as surrogate marker of insulin resistance, obesity, hirsutism and hypothyroidism in PCOS women have been simultaneously studied. Materials and Methods: Present work is a non comparative cross-sectional open label study carried out over a period of 18 months in an endocrinology hospital in western Maharashtra, India. Results and Conclusion: Authors conclude that PCOS occurs both in obese and non-obese women; AN and hirsutism occur in equal proportion of patients. AN is correlated with obesity. Hormonal dysfunctions in PCOS manifested together or independently. PCOS women can be sub grouped based on clinical features suggestive of endocrinological malfunctions and can be investigated accordingly for selection of appropriate treatment modalities.